Adolescent Self-Control and Individual Physical and Mental Health in Adulthood: A Chinese Study - Yang, Fan; Jiang, Yao (Frontiers in Psychology, 2022)
Despite its association with individual health, few studies have focused on the relationship between adolescent self-control and individual physical and mental health in adulthood. We aimed, therefore, to explore the impact of adolescent self-control on individual physical and mental health in adulthood. We employed the dataset of China Labor-Force Dynamics Surveys (CLDS) 2016. 13,389 respondents with an average age of 45.621 years are consisted in this study. The respondents were asked to report their adolescent self-control through recall. The ordered probit and the ordinary least squares (OLS) models were employed to estimate the effects of adolescent self-control on physical and mental health in adulthood, respectively. We adopted the propensity score matching (PSM) method to address the self-selection bias of samples. The results indicated that adolescent self-control significantly affected individual physical health (coefficient = 0.0126, p < 0.01) and mental health (coefficient = -0.1067, p < 0.01) in adulthood. The mechanism analysis suggested that adolescent self-control partially promoted physical and mental health in adulthood by education and income instead of self-control in adulthood. In conclusion, paying attention to the cultivation of self-control before adulthood may be an effective way to improve individual physical and mental health in adulthood.